Good Governance Practices In Archipelagic Regional Administration: Praktik Tata Kelola Pemerintahan Di Wilayah Kepulauan - Rizky Ramadhanu; Ghazwan Hakim; Vina Amanda (Academia Open, 2026)
General Background: Good governance constitutes a fundamental framework for public administration aimed at ensuring transparency, accountability, participation, and justice within governmental processes. Specific Background: In Indonesia, regional governments with archipelagic characteristics face distinct administrative and geographic challenges, particularly in public service distribution, access to information, and citizen participation, as experienced by the Riau Islands Province. Knowledge Gap: Existing studies predominantly examine good governance within continental or urban contexts, while empirical analysis focusing on archipelagic regional governance remains limited. Aims: This study analyzes the application of good governance principles in regional government administration in the Riau Islands Province and identifies supporting factors, constraints, and governance-strengthening strategies aligned with archipelagic conditions. Results: The findings indicate that transparency is pursued through public information disclosure and digital governance initiatives, accountability is implemented via performance evaluation mechanisms and the Government Agency Performance Accountability System, and public participation is facilitated through development planning forums; however, persistent challenges include corruption practices, low public literacy, digital disparities, and uneven bureaucratic capacity. Novelty: This research offers a governance framework specifically formulated for archipelagic regions by integrating service-oriented bureaucratic reform, digital transformation, and multi-stakeholder collaboration. Implications: The study provides contextual insights for regional policymakers in designing governance arrangements that align with archipelagic administrative realities and support transparent, accountable, and sustainable regional administration. Highlights • Transparency initiatives rely on public information disclosure and digital governance systems• Accountability mechanisms remain predominantly procedural due to limited public engagement• Archipelagic governance requires integrated bureaucratic reform and digital coordination Keywords Good Governance; Regional Government; Archipelagic Area; Digital Governance; Public Administration